2015
DOI: 10.1590/s0036-46652015000600002
|View full text |Cite
|
Sign up to set email alerts
|

PATHOGENICITY OF Blastocystis sp. TO THE GASTROINTESTINAL TRACT OF MICE: RELATIONSHIP BETWEEN INOCULUM SIZE AND PERIOD OF INFECTION

Abstract: The pathogenic potential of Blastocystis sp. in experimental models requires further investigation. In this work, the pathogenicity of this parasite in the gastrointestinal tract of male Swiss mice was evaluated according to the inoculum size and period of infection. Animals were infected intragastrically, with 100, 500, 1,000, 5,000 and 10,000 Blastocystis sp. vacuolar forms obtained from a mixture of eight human isolates cultured axenically in Jones' medium. After seven, 14, 21, 28 and 60 days of infection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
3
16
0
1
Order By: Relevance
“…Thus, caution should be observed when choosing a suitable animal model to study blastocystosis. In our animal experimental study, and as previously reported [28,29,43,44] , 3 weeks-old mice were used successfully to produce blastocystosis. All Blastocystis spp.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Thus, caution should be observed when choosing a suitable animal model to study blastocystosis. In our animal experimental study, and as previously reported [28,29,43,44] , 3 weeks-old mice were used successfully to produce blastocystosis. All Blastocystis spp.…”
Section: Discussionsupporting
confidence: 61%
“…In the present work, experimental blastocystosis was successfully induced in all BALB-c mice by intragastric inoculation with 1.0×10 5 Blastocystis organisms in100 μl saline. In the work of El Wakil and Hewedy [28], similar inoculum doses produced infection in only 40% of the animals while in the work of Pavanelli et al [44] , a smaller inoculum of 1.0 x 10 2 produced infection in all animals. These variations may be due to differences in infectivity of Blastocystis spp.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations